Theatres of Agitation ... - Westerside, Andrew (University of Lincoln, 2024)
Theatres of Agitation: Performing Politics on the 21st Century Stage (2015-2018)This three-year research project was a collaboration between Dr Andrew Westerside (University of Lincoln, Principal Investigator) and Proto-type Theater (Co-I, partner)The project took as its starting point a critical (practice-led) study into the development of practical methodologies for staging affective radical and resistance politics on contemporary British Stages.Research Imperatives/Questions:1. Is it possible to determine, through studio-led research processes, practical and replicable methodologies for staging radical or agitational political discourse on contemporary British stages?2. How might those methodologies be used to create touring performance works such that their efficacy can be tested against the sector?Research Outputs1. Performance: A Machine They’re Secretly Building (2016) (writer, director: Andrew Westerside) (Eprint ID: 23365)2. Performance: The Audit (or Iceland, a modern myth) (2018) (writer, ...